Persuasive Strategies Used by the Coaches in the Blind Audition of The Voice USA 2018 - Nur, Serliah; Jannah, Rika Nur; Rauf, Masykur (Journal of Islamic Culture and Literature (JICeL), 2020)
This article discusses the persuasive strategies used by the coaches in the blind audition of The Voice USA 2018. The objects of this research are the utterances of the four coaches in The Voice USA 2018 who are Adam Levine, Alicia Keys, Kelly Clarkson, and Blake Shelton. The objectives of this research are to identify the kinds of persuasive strategies and to analyze the way the persuasive strategies were expressed by the coaches in the blind audition of The Voice USA 2018. This research used a descriptive qualitative method. The data sources in this research are videos and transcripts. The researcher took twelve videos of the blind audition of the Voice USA 2018 which have more than three million views on YouTube as the sources of data. The researcher took the data from the official YouTube account of The Voice. In collecting the data, the researcher watched all the twelve videos of the blind audition of The Voice USA 2018 from the official YouTube account of The Voice and transcribed the videos. The instrument that is used in this research is the researcher herself as the instrument to get the data. The results of the research show that the four coaches in the blind audition of The Voice USA 2018 used three persuasive strategies which are logos, ethos, and pathos. The way of the coaches used the three strategies was different. When stating logos, the coaches persuaded the contestants by stating logical reasons, a specific fact, and truths as a piece of supporting evidence. When they used ethos, they showed their reputation, credibility, image, character, and the previous record to get more trust from the contestants. Then, when they used pathos, they used emotional appeal to control the contestants' emotions. Keywords: Logos, Phatos, Ethos, Blind Audition